Dinamika Pola Komunikasi Keluarga dan Implikasinya terhadap Pembentukan Pemahaman Anak tentang Kesetaraan Gender - Siga, Marianus; Hago, Maria Mirayanti; Kontesa, Agnesia Fifin; Mas’ud, Fadil (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2025)
The dynamics of family communication play an important role in shaping children's understanding of gender equality, especially in the context of a society that still internalizes traditional gender stereotypes. Parents often unconsciously reproduce gender biases through everyday interactions, both verbally and through the division of domestic tasks. This study aims to analyse the influence of family communication patterns on the formation of children's understanding of gender equality, as well as to identify forms of family communication that support or hinder this understanding. The method used is a literature review of Indonesian research in the last five years related to family communication and gender socialization.  The study results indicate that open, dialogic, empathetic, and stereotype-free communication enhances children's understanding of gender equality. Conversely, authoritarian, rigid communication, as well as inconsistencies between words and actions, tend to perpetuate unequal gender patterns. These findings emphasize the importance of family communication practices that are inclusive and gender sensitive as a foundation for internalizing the values of equality from an early age.